UNCONSCIOUS PERCEPTION BY ATHLETES OF NEGATIVE INCENTIVES ASSOCIATED WITH COMPETITIVE ACTIVITY - Golub Ya.V. ,; Ageev E.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the influence of late evoked potentials N200, P300 on the unconscious perception of negative stimuli, using the example of words associated with competitive activity in conditions of disguise using the example of martial arts. Methods and structure of the study. Participants were asked to count the number of presentation signals that appeared on the monitor, which masked short-term stimuli. The study protocol was the study of late evoked potentials - N200 (150-350 ms) and P300 (250-400 ms). Neutral and negative (emotionally significant) words characterizing competitive activity were used as stimulus material. The following words were classified as neutral: SUMMER, AUTUMN, WINTER, SPRING, SKY. The following words were classified as negative: FAIL, DEFEAT, PAIN, INJURY, KNOCKOUT. Each word was presented five times. A total of 30 stimuli were presented in each trial. Stimuli were presented in the center of the screen in an unconscious mode with the presentation of a masking indifferent signal. The screen remained blank between stimuli. The duration of the stimulus was 30 ms; the duration of the masking signal was 373 ms; the interstimulus interval was 800 ms. Results and conclusions. An increase in the latent time and amplitude of late evoked potentials N200 and P300 was found in response to the presentation of negative words under masking conditions, compared with neutral words. Unconscious perception of negative (emotionally significant) words leads to an increase in the analysis time and additional involvement of cognitive reserves. This phenomenon can be reflected in our further studies devoted to the assessment of the athletes' unconscious perception of competitive activity.